Mobile life and family. The impact of ICTs on spatial-geographic mobility. - García-Moreno, José Manuel (Wiley, 2021)
The family is in a constant process of adaptation to the structural changes brought about by the network society, such as the digitalization of social relationships as a result of the extension of Information and Communication Technologies (ICTs). The aim of this study is to examine the process of spatial-geographic mobility in Spain supported by ICTs within the family. To meet this objective, data from two studies by the Spanish Center for Sociological Research (2015 and 2016) focused on understanding the Impact of ICTs on the Family in Spain were analyzed. The results indicate that the probability of moving geographically is greater when instant messaging software and digital social networks are used within the family. Differences are found in sociodemographic and social status factors. The probability of moving geographically increases when the use of ICTs enables families to become more efficient and competent and when their social capital increases.
This is the accepted version of the following article: Garcia Moreno, J. M. (2021). Mobile life and family. The impact of ICTs on spatial-geographic mobility. Population, Space and Place, 27(8), e2454, which has been published in final form at https://doi.org/10.1002/psp.2454 This article may be used for noncommercial purposes in accordance with the Wiley Self-Archiving Policy: http://www.wileyauthors.com/self-archiving.
https://openpolicyfinder.jisc.ac.uk/id/publication/7550?from=single_hit
Keywords: Familias - Movilidad geográfica; Tecnologías de la información y la comunicación; Family; Spatial and geographic mobility; Information and communication technologies; Social networks; Digital networks; Familia; Movilidad geográfica; Redes sociales; Redes digitales